Multi‐echo MR thermometry in the upper leg at 7 T using near‐harmonic 2D reconstruction for initialization - Kikken, Mathijs W. I.; Steensma, Bart R.; Berg, Cornelis A. T.; Raaijmakers, Alexander J. E. (Magnetic resonance in medicine, 2023)
Purpose The aim of this work is the development of a thermometry method to measure temperature increases in vivo, with a precision and accuracy sufficient for validation against thermal simulations. Such an MR thermometry model would be a valuable tool to get an indication on one of the major safety concerns in MR imaging: the tissue heating occurring due to radiofrequency (RF) exposure. To prevent excessive temperature rise, RF power deposition, expressed as specific absorption rate, cannot exceed predefined thresholds. Using these thresholds, MRI has demonstrated an extensive history of safe usage. Nevertheless, MR thermometry would be a valuable tool to address some of the unmet needs in the area of RF safety assessment, such as validation of specific absorption rate and thermal simulations, investigation of local peak temperatures during scanning, or temperature‐based safety guidelines. Methods The harmonic initialized model‐based multi‐echo approach is proposed. The method combines a previously published model‐based multi‐echo water/fat separated approach with an also previously published near‐harmonic 2D reconstruction method. The method is tested on the human thigh with a multi‐transmit array at 7 T, in three volunteers, and for several RF shims. Results Precision and accuracy are improved considerably compared to a previous fat‐referenced method (precision: 0.09 vs. 0.19°C). Comparison of measured temperature rise distributions to subject‐specific simulated counterparts show good relative agreement for multiple RF shim settings. Conclusion The high precision shows promising potential for validation purposes and other RF safety applications.